"Where does the fluorescing moiety reside in a carbon dot?" – Investigations based on fluorescence anisotropy decay and resonance energy transfer dynamics. Issue 4 (5th January 2018) - Das, Ananya; Roy, Debjit; De, Chayan K.; Mandal, Prasun K.
Abstract : It has been shown recently that aggregated dyes are responsible for very high fluorescence in a carbon dot (CD). Location of the fluorescing unit in a carbon dot could be shown. Abstract : It has been shown recently that aggregated dyes are responsible for very high fluorescence in a carbon dot (CD). However, what is the location of the fluorescing moiety in CD? Is it inside the CD or attached to the CD's surface? In order to answer these intriguing questions regarding the location of the fluorescing moiety in a CD, we performed rotational anisotropy decay dynamics and resonance energy transfer (RET) dynamics. Rotational correlation time of ∼120 picoseconds nullifies the fact that the whole CD is fluorescing. Instead, we can say that the fluorescing moiety is either embedded inside the CD or attached to the surface of the CD or linked to the CD through covalent bonds. From the fluorescence anisotropy decay dynamics in solvents of different viscosities, we could show that the fluorescing moiety is not attached to the surface of the CD or for that matter, the fluorescing moiety is not in a rigid environment inside the CD. RET dynamical analysis has shown that the time for RET (from CD to acceptor Rh123) is about 5.4 ns and the RET dynamics are independent of the acceptor concentration. Using RET dynamics, we could prove that the fluorescing moiety is not outside the CD; rather, it is inside the CD, but not in a rigid environment. The geometric distance between the fluorescing moiety of the CD and the acceptor (Rh123) has been obtained to be 4.55 nm. Using Förster formulation, the distance between the fluorescing moiety inside the CD and the acceptor Rh123 has been calculated to be 4.24 nm. Thus, we could not only reveal the exact location of the fluorescing moiety in a CD, but we could also demonstrate that unlike for many other nanomaterials, Förster formulation could explain the experimental observables regarding RET involving CD reasonably well.